2019
DOI: 10.1186/s42358-019-0095-3
|View full text |Cite
|
Sign up to set email alerts
|

Relation between magnesium and calcium and parameters of pain, quality of life and depression in women with fibromyalgia

Abstract: Objective: Determine food intake and levels of serum magnesium (Mg) and calcium (Ca) and correlate these minerals with pain, quality of life and depression risk in women with and without fibromyalgia (FM). Patients and methods: Fifty-three women diagnosed with FM and 50 healthy women participated in the study, where all of them had equivalent age and body mass index (BMI). All women underwent anthropometric assessment, physical exams of pain perception threshold and tender point (TP) count, blood sample collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…Several reports showed no difference in magnesium levels between fibromyalgia and control subjects, with no correlation between magnesium levels and fibromyalgia parameters. 28 - 31 Andretta et al 28 , 29 and Sakarya et al 30 found no significant differences in the serum levels of magnesium between fibromyalgia patients and control subjects. 28 - 30 One of the studies performed by Andretta et al, 28 showed no correlation between serum magnesium levels and pain, quality of life, and depression risk in the fibromyalgia group.…”
Section: Resultsmentioning
confidence: 95%
“…Several reports showed no difference in magnesium levels between fibromyalgia and control subjects, with no correlation between magnesium levels and fibromyalgia parameters. 28 - 31 Andretta et al 28 , 29 and Sakarya et al 30 found no significant differences in the serum levels of magnesium between fibromyalgia patients and control subjects. 28 - 30 One of the studies performed by Andretta et al, 28 showed no correlation between serum magnesium levels and pain, quality of life, and depression risk in the fibromyalgia group.…”
Section: Resultsmentioning
confidence: 95%
“…As its causes are unclear, multiple treatments including pharmacologic agents and non-pharmacologic therapies are used to manage widespread pain [ 95 ]. Several studies investigated the relationship between the elemental composition of the body and clinical parameters in patients with fibromyalgia [ 96 , 97 , 98 ]. They presented low magnesium levels versus normal controls [ 96 , 97 ].…”
Section: Other Acute and Chronic Painmentioning
confidence: 99%
“…They presented low magnesium levels versus normal controls [ 96 , 97 ]. In addition, the dietary intake of magnesium was lower in patients presenting with fibromyalgia [ 98 ]. Magnesium deficiency can increase levels of substance P, which is related to the pain intensity of fibromyalgia [ 99 , 100 , 101 ].…”
Section: Other Acute and Chronic Painmentioning
confidence: 99%
“…Magnesium deficiencies were largely associated with low-grade inflammation, muscle weakness and paresthesia, which are typical symptoms of FM [21]. A recent study has shown that low dietary magnesium intake is correlated with worsening pain threshold parameters in FM patients [43]. Magnesium has always been considered the nonpharmacological supplement with the highest potential for FM [44]; however, so far, only two clinical trials have been performed in FM patients.…”
Section: Mineralsmentioning
confidence: 99%